Government Public Relations: Opportunities and Challenges in Socializing the Mayor's Regulation on Parking Price Reduction in Pekanbaru City - Amalia, Risa; Nurjanah, Nurjanah; Rasyid, Anuar (Journal of Governance, 2025)
This study aims to analyze the role of Government Public Relations (GPR) of the Pekanbaru City Government in disseminating Mayor Regulation Number 2 of 2025 concerning the Review of Public Service Retribution Rates for On-Street Parking Services, as well as to identify the opportunities and challenges encountered in the dissemination process. The background of this research is based on the importance of effective public communication in supporting the implementation of regional policies, especially those directly affecting public interests. This study employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews with the Public Relations division of the Pekanbaru City Government, field observations, and documentation related to the policy dissemination process. The findings reveal that the communication strategy of the Public Relations Division in disseminating Mayor Regulation Number 2 of 2025 regarding the reduction of parking fees involves an integrated approach that combines traditional and digital media, clear and visual messaging, and participatory discussion forums. This approach aims to increase public awareness, compliance, and participation, as well as to build public trust in the government. However, the challenges faced include reaching a heterogeneous audience, combating misinformation, simplifying complex information, adapting to technological developments, and managing limited resources. With inclusive and adaptive strategies, it is expected that the policy can be well-received and effectively implemented by the community.